Designing English Reading Text Based on Herritage Historical - Pelawi, Riana Br; Pakpahan, Emma Martina; Pakpahan, Carolina Mutiara (ELT (English Language Teaching Prima Journal), 2022)
The lack of new reading material is one of the factors reducing students' interestin reading. This makes this research focus on adding reading material withdescriptive text by raising an object that is rarely exposed. The object of thisresearch is taken from historical relics around which students rarely know.Therefore, this study aims to design an interesting reading material based onhistorical heritage and expose local heritage historical that is still rarely known.This study uses a qualitative method with a descriptive approach. The researchlocation is the Benteng Putri Hijau site located in North Sumatra Province, DeliSerdang Regency. This study uses primary and secondary data collectiontechniques. This research spent a week to collect related data sources. Thisresearch succeeded in creating a new, varied reading material for the tenth gradeX students of SMK 2 TELKOM MEDAN.Heritage Historical,motivating,reading interesting